The Ignition Behaviour of Energetic Materials Under Confined Cookoff - Stennett, Christopher (Cranfield University, 2018)
In a series of experiments and theoretical work, the process of ignition in confined energetic materials has been explored and understanding gained. Early work focused on the direct observation of the cook-off process but was hampered by the available technology. In more recent work, dynamic measurements of the deformation of the confinement have been explored, and refinements to the direct observation method have been made that make use of recent advances in camera technology. We have observed, for the first time, complex melting and development of gas spaces within which the early stages of ignition take place, and propose a new mechanism by which violent cook-off responses might develop in certain explosives
© Cranfield University 2018. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner
Keywords: Cook-off process